Empires of ancient Eurasia : the first Silk Roads era, 100 BCE - 250 CE - Benjamin, Craig (New approaches to Asian history, 2018)
"The Silk Roads are the symbol of the interconnectedness of ancient Eurasian civilizations. Using challenging land and maritime routes, merchants and adventurers, diplomats and missionaries, sailors and soldiers, and camels, horses and ships, carried their commodities, ideas, languages and pathogens enormous distances across Eurasia. The result was an underlying unity that traveled the length of the routes, and which is preserved to this day, expressed in common technologies, artistic styles, cultures and religions, even disease and immunity patterns"--